2022
DOI: 10.1038/s41467-022-34205-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial membrane proteins and VPS35 orchestrate selective removal of mtDNA

Abstract: Understanding the mechanisms governing selective turnover of mutation-bearing mtDNA is fundamental to design therapeutic strategies against mtDNA diseases. Here, we show that specific mtDNA damage leads to an exacerbated mtDNA turnover, independent of canonical macroautophagy, but relying on lysosomal function and ATG5. Using proximity labeling and Twinkle as a nucleoid marker, we demonstrate that mtDNA damage induces membrane remodeling and endosomal recruitment in close proximity to mitochondrial nucleoid su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 78 publications
3
37
0
Order By: Relevance
“…While VDAC and MICOS-MIB complexes were slightly increased, the prohibitin complex displayed a downward mass shift without a change in intensity. These observations likely depict the reorganization of mitochondrial membrane architecture in response to EtBr-induced stress and mtDNA depletion (74,75).…”
Section: Mitochondrial Gene Expression Rapidly Recovers After Removal...mentioning
confidence: 88%
“…While VDAC and MICOS-MIB complexes were slightly increased, the prohibitin complex displayed a downward mass shift without a change in intensity. These observations likely depict the reorganization of mitochondrial membrane architecture in response to EtBr-induced stress and mtDNA depletion (74,75).…”
Section: Mitochondrial Gene Expression Rapidly Recovers After Removal...mentioning
confidence: 88%
“…Also, several endosomal-dependent mitophagy pathways have recently been described, including studies involving vesicles positive for Rab5 38 , Rab7 48 , Rab11A 49 , or CARP2 50 . More recently, it has been reported that a component of the retromer responsible to transport select cargo between different endosomes, VPS35, is involved in an mtDNA-selective degradation process in conditions where mtDNA holds mutations 51 .…”
Section: Discussionmentioning
confidence: 99%
“…ATAD3A is a conserved AAA+ ATPase that regulates mitochondrial inner membrane architecture. It spans the IMM with its C-terminus facing the matrix and associating with the nucleoids (Gilquin et al, 2010; Ishihara et al, 2022; Sen et al, 2022) (Figure S9A). We surmised that ATAD3A might link nucleoids comprising defective genomes with mitochondrial membranes.…”
Section: Resultsmentioning
confidence: 99%